POWER ANALYSIS OF FORESTRY CUTTERS FOR COMMINUTING OF WOOD WASTE IN POPLAR CLEARINGS. PART 2: POWER PARAMETERS - Marinov, Konstantin (Innovation in Woodworking Industry and Engineering design, 2019)
Forest milling machines have high technological properties but also higher energy consumption and higher power requirements. In the present study, a theoretical analysis is performed to determine the power required for propulsion of specialized forest milling machines used for soil preparation of poplar clearings. For this purpose appropriate analytical dependencies are developed to define the required power of forest milling cutters for comminuting left slash and tree-shrub vegetation in fresh poplar cleaning, and shallow soil tilling. A new formula has been developed for a more complete definition of the power balance equation of forest milling aggregates for soil preparation. A suitable theoretical-experimental model for the determination of dynamic parameters in analytical dependencies is proposed.